Application Of Factorial Design To The Stress Phenomenon Of Bacillus Cereus (Atcc 14579) Growth - Ahmad, Mani Malam; Abdul Aziz, Mohd Azoddein; Mior Ahmad Khushairi, Mohd Zahari; Mazrul Nizam, Abu Seman (AENSI Publishing, 2016)
Background: A two level (23) factorial design of experiment (DOE) was employed to investigate the influence of nutrients concentrations and main operational parameters on the growth of Bacillus cereus (ATCC 14579) in a shake flask. The factorial models have been established from experimental design to study the individual and interactions effects toward the response within the selected variables nutrient concentration (4-16gl-1), temperature (300C – 420C), agitation (140rpm-200rpm) and acclimatization time (24hours-72hours). These were statistically validated using analysis of variance (ANOVA). Objective: The present study aimed to use fractional factorial design of experiment to investigate the influence of growth limiting factors to the bacterial growth in a fermenting medium of orbital shaker. Results: The results revealed that the model terms were all significant with F-value of 251.07 at (p <0.004). The model term having the most significant effect on the response was nutrient concentration. And the magnitude of the main influence is in the ascending order nutrient concentration > temperature > acclimatization time. The analysis of the experimental response indicated that the interaction of nutrient concentration and temperature had the highest influence on the response. Whereas the interaction effects of nutrient and acclimatization time was found to be statistically insignificant. Based on the R2 and adjusted R2 the estimated model terms spell high degree of relationship between observed and predicted values, thus the prediction ability of the models is maintained. Conclusion: Although the interaction models terms have significant effects, their levels were only less likely comparable to linear effects. It could therefore concluded that nutrient concentration, temperature and to some extend acclimatization time were four to greatly limit growth at a specific ranges. In general, the predicted value was in reasonable agreement with the experimental data, further confirming the very good prediction ability of the model.